2016
DOI: 10.1007/s10552-016-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between hematopoietic growth factors and risks of venous thromboembolism, stroke, ischemic heart disease and myelodysplastic syndrome: findings from a large population-based cohort of women with breast cancer

Abstract: Receipts of CSFs and ESAs were significantly associated with an increased risk of VTE in women with breast cancer. Use of ESAs was significantly associated with substantially increased risks of MDS. These findings support those of previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The use of CSFs and ESAs has definitely improved the effectiveness of chemotherapy treatments, although several observational and randomized studies have indicated that these HGFs had some short- and long-term side effects in several cancer pathologies (120,121). Among these side-effects are venous thromboembolism (VTE), stroke, ischemic heart disease and AML or myelodysplastic syndrome (MDS) in patients with various types of cancer, including breast cancer (120-122).…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of CSFs and ESAs has definitely improved the effectiveness of chemotherapy treatments, although several observational and randomized studies have indicated that these HGFs had some short- and long-term side effects in several cancer pathologies (120,121). Among these side-effects are venous thromboembolism (VTE), stroke, ischemic heart disease and AML or myelodysplastic syndrome (MDS) in patients with various types of cancer, including breast cancer (120-122).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Du and Zhang (2015) and Du et al (2016) evaluated the association between the use of CSFs and ESAs and the increased risk of VTE, stroke, ischemic heart disease and AML/MDS onset in patients with breast and colorectal cancers (120,121). These authors demonstrated that patients with colorectal cancer treated with chemotherapy combined with CSFs and ESAs had an increased risk of MDS, VTE and to a lesser extent, an increased risk of ischemic heart disease (120).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 22 studies that reported the combined incidence of ischemic and hemorrhagic stroke at 1 year, eight were cohort studies that included multiple types of cancer ( Supplementary Figure 3 ) ( 12 , 14 , 15 , 25 , 27 , 31 , 33 , 34 ). The remaining 14 studies were limited to specific cancer subtypes including head and neck cancer ( n = 3) ( 16 , 24 , 28 ), hematologic malignancies ( n = 2) ( 19 , 29 ), breast cancer ( n = 2) ( 21 , 23 ), and thyroid cancer ( n = 2) ( 26 , 32 ). There was only one study for each of the following subtypes of cancer: pancreatic, cervical, prostate, colorectal, and hepatic ( 17 , 18 , 20 , 22 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…(P <0.0001) (21). Since then, a series of studies have demonstrated that the application of G-CSF is associated with an increased risk of VTE in patients with gastroesophageal (30), colorectal (31), breast (32), and comprehensive cancers (33).…”
Section: Figurementioning
confidence: 99%